Effect of maternal age and body mass index on induction of labor with oral misoprostol for premature rupture of membrane at term: A retrospective cross-sectional study - Sfregola Gianfranco; Sfregola Pamela; Ruta Federico; Zendoli Federica; Musicco Alessandra; Garzon Simone; Uccella Stefano; Etrusco Andrea; Chiantera Vito; Terzic Sanja; Giannini Andrea; Laganà Antonio Simone (Open Medicine, 2023)
The aim of this study was to evaluate the effect of maternal age and body mass index (BMI) on induction of labor with oral misoprostol for premature rupture of membrane (PROM) at term. We have conducted retrospective cross-sectional study, including only term (37 weeks or more of gestation) PROM in healthy nulliparous women with a negative vaginal-rectal swab for group B streptococcus, a single cephalic fetus with normal birthweight, and uneventful pregnancy that were induced after 24 h from PROM. Ninety-one patients were included. According to the multivariate logistic regression, age and BMI odds ratio (OR) for induction success were 0.795 and 0.857, respectively. The study population was divided into two groups based on age (<35 and ≥35 years) and obesity (BMI <30 and ≥30). Older women reported a higher induction failure rate (p < 0.001); longer time to cervical dilation of 6 cm (p = 0.03) and delivery (p < 0.001). Obese women reported a higher induction failure rate (p = 0.01); number of misoprostol doses (p = 0.03), longer time of induction (p = 0.03) to cervical dilatation of 6 cm (p < 0.001), and delivery (p < 0.001); and higher cesarean section (p = 0.012) and episiotomy rate (p = 0.007). In conclusion, maternal age and BMI are two of the main factors that influence oral misoprostol efficacy and affect the failure of induction rate in term PROM.